2016
DOI: 10.14419/ijbas.v5i2.6047
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the predictive and prognostic values of polymorphism of some cell cycle genes in breast cancer

Abstract: Aim: To investigate the influence of the polymorphic variants of CCND1 (G870A) and p73 (G4C14-to-A4T14) on the susceptibility to breast cancer development, also, to figure out their diagnostic and prognostic roles. Subjects and Methods: Blood samples were obtained from breast cancer patients and controls. Genotyping of CCND1 and p73 genes were carried out by PCR-RFLP and PCR-CTPP; respectively. Results: In comparison with the control group, CCND1 (G870A) GA and AA genotypes frequencies were significantly highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Fifty-five case–control studies 2 , 24 74 including 15,648 cancer cases and 19,159 controls met the eligibility criteria and were finally included in this meta-analysis ( Figure 1 ). A total of 194 studies were excluded after screening the title, abstract and full-text, because of irrelevant information, incomplete genetic data, or duplicate contents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifty-five case–control studies 2 , 24 74 including 15,648 cancer cases and 19,159 controls met the eligibility criteria and were finally included in this meta-analysis ( Figure 1 ). A total of 194 studies were excluded after screening the title, abstract and full-text, because of irrelevant information, incomplete genetic data, or duplicate contents.…”
Section: Resultsmentioning
confidence: 99%
“…Decreased expression of p73 mRNA was identified in both inflammatory and non-inflammatory BC cells compared with normal breast epithelial cells, indicating that this variant might increase the risk of BC by reducing the expression of p73. A recent study postulated that the TP73 GC/AT and AT/AT genotypes could increase the susceptibility to BC, while another study found that the GC/GC genotype was associated with an increased risk of triple-negative BC, 2 , 37 , 66 and yet another study found no significant association between this polymorphism and BC. 62 Similar findings were observed in EC studies with contradictory conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation